An Analysis of Troubled Youth: An Achievement Motivation Perspective - Freeman, Brenda; Schopen, Ann (Canadian Journal of Counselling and Psychotherapy, 2007)
This study investigates the attribution of success and failure in five naturally occurring clusters of seventh grade students Popular Insiders, Ambitious Insiders, Outsiders, Alienated Disengaged, and Invisible Students. Participants included 217 seventh grade students accessed through a random selection of required English classes. Descriptive statistics and Analysis of Variance are used to discuss achievement attributions of each cluster. The authors take the position that school counsellors need to understand achievment related behaviour, because achievement is central to the mission of schools. Implications for school counsellors are discussed, with an emphasis on helping troubled youth (Outsiders and Alienated Disengaged).